Evolution of the production’s organization and social structure in Globalization. - Palomo Garrido, Aleksandro (Nómadas. Critical Journal of Social and Juridical Science, 2017)
In the nineties there was a global process of production reorganization. On the one hand , this reorganization occurred due to technological reasons . Corporations decided to invest in equipment renewal and application of new technologies. On the other hand , governments decided to open the borders . This reorganization of production had global social consequences that have evolved along Globalization. In this paper, we analyze this process and the resulting social structure until 2008 crisis